Transparansi Pengelolaan Keuangan Desa dalam Pembangunan Infrastruktur di Desa Tanete Kecamatan Maritengngae Kabupaten Sidenreng Rappang - Aeni, Nur; Putri P, Andi Sri Kumala; Yahya, Yahya (Paser Institute Of Accounting and Finance, 2025)
The problem in this study stems from the low public understanding of transparency in village financial management, despite the village government practicing openness. This research aims to examine the extent to which transparency is implemented in infrastructure development in Tanete Village and how financial management mechanisms are applied. The study uses a descriptive qualitative approach with a phenomenological method, employing observation, interviews, and documentation with village officials and community members. The findings indicate that transparency efforts have been made through open access todocuments, information dissemination, and public participation in deliberations. However, challenges remain in community literacy and the effectiveness of information delivery. This study highlights the importance of effective communication and active community participation to achieve transparent and accountable village financial governance.